Methane Elimination Using Biofiltration Packed With Fly Ash Ceramsite as Support Material - Sun, Meng-Ting; Zhao, Yu-Zhong; Yang, Zhi-Man; Shi, Xiao-Shuang; Wang, Lin; Dai, Meng; Wang, Fei; Guo, Rong-Bo (Frontiers in Bioengineering and Biotechnology, 2020)
Methane is a greenhouse gas and significantly contributes to global warming. Methane biofiltration with immobilized methane-oxidizing bacteria (MOB) is an efficient and eco-friendly approach for methane elimination. To achieve high methane elimination capacity (EC), it is necessary to use an exceptional support material to immobilize MOB. The MOB consortium was inoculated in biofilters to continuously eliminate 1% (v/v) of methane. Results showed that the immobilized MOB cells outperformed than the suspended MOB cells. The biofilter packed with fly ash ceramsite (FAC) held the highest average methane EC of 4.628 g h-1 m-3, which was 33.4% higher than that of the biofilter with the suspended MOB cells. The qPCR revealed that FAC surface presented the highest pmoA gene abundance, which inferred that FAC surface immobilized the most MOB biomass. The XPS and contact angle measurement indicated that the desirable surface elemental composition and stronger surface hydrophilicity of FAC might favor MOB immobilization and accordingly improve methane elimination.